Penggunaan Seni Rupa Kaligrafi Dalam Pendidikan Islam - Windy Aprilia (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
Art is a beautiful skill. Calligraphy is a unique, beautiful and interesting writing art. Calligraphy is also known as "the art of Islamic art". Calligraphy can be used as a medium of learning in Islam. In addition, the art of calligraphy can also be used as material or teaching material for the learning process of Islamic religious education. Calligraphy can help students to form a good personality. Therefore, the art of calligraphy can be used by educators as a medium of da'wah in education. Which is where calligraphy is a culture that is identical to Islam.